2017
DOI: 10.1590/10.1590/0102-311x00015017
|View full text |Cite
|
Sign up to set email alerts
|

Diferenciais de mortalidade entre indígenas e não indígenas no Brasil com base no Censo Demográfico de 2010

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
29

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 9 publications
(10 reference statements)
0
16
0
29
Order By: Relevance
“…According to the 2010 Brazilian National Census, the indigenous population (896 917) represented just 0.4% of the national population, which is among the smallest by proportion in Latin America. This demographic group carries a disproportionately heavy burden of both infectious and noninfectious chronic diseases (Anderson et al, ) and has much higher mortality levels than nonindigenous people (Campos, Borges, Queiroz, & Santos, ). Underfunded health services lacking appropriate intercultural sensitivity aggravate this discouraging scenario.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2010 Brazilian National Census, the indigenous population (896 917) represented just 0.4% of the national population, which is among the smallest by proportion in Latin America. This demographic group carries a disproportionately heavy burden of both infectious and noninfectious chronic diseases (Anderson et al, ) and has much higher mortality levels than nonindigenous people (Campos, Borges, Queiroz, & Santos, ). Underfunded health services lacking appropriate intercultural sensitivity aggravate this discouraging scenario.…”
Section: Introductionmentioning
confidence: 99%
“…For the 2009-2010 period, Caldas et al [69] reported significantly higher infant mortality rates for the Indigenous population (47.2 deaths per thousand live births according to the SIM data and 27.3 per thousand according to the 2010 Census) when compared to the figures for the Brazilian population overall (16.3 and 15.9 per thousand, respectively) [69]. Based on the data on deaths collected by the 2010 Census, Campos et al [70] investigated the probability of death in the Indigenous and non-Indigenous population according to gender in three age groups (0-4.9, 5 to 9.9 and 15 to 44.9 years), observing that the figures were always higher for men and for Indigenous people, sometimes as high as double among the first two age groups [70].…”
Section: Ruralmentioning
confidence: 99%
“…Emphasizing the need for better knowledge of the mortality levels of Indigenous peoples in Brazil, some recent studies have given special attention to analysing data representative at a national scale, such as the information derived from the SIM and the 2010 Census [69,70]. For the 2009-2010 period, Caldas et al [69] reported significantly higher infant mortality rates for the Indigenous population (47.2 deaths per thousand live births according to the SIM data and 27.3 per thousand according to the 2010 Census) when compared to the figures for the Brazilian population overall (16.3 and 15.9 per thousand, respectively) [69].…”
Section: Ruralmentioning
confidence: 99%
“…Em relação à mortalidade, há escassez de estudos para a população indígena do país. Estimativas baseadas nos dados de óbitos do Censo Demográfico de 2010 apontam maiores taxas entre indígenas do que entre não indígenas, em todos os grupos etários e em ambos os sexos, sobretudo em mulheres e crianças 14 . Em se tratando da mortalidade por câncer não existem dados com representatividade nacional e poucos estudos demográficos foram realizados em etnias específicas 15,16,17,18 .…”
Section: Introductionunclassified